Loss of chemical bonds induced by high doses of γ-radiation in a PADC polymer film: The influence of dose and dose rate on radiation chemical yields. (October 2021) - Saad, A.F.; Fromm, M.; Ibraheim, Mona H.; El-Namrouty, A.A.; Nwara, Aya M.; Kandil, S.A.; Dawood, Mahmoud S.
Abstract: The effects of gamma rays on molecular properties of a poly allyl diglycol carbonate (PADC) polymer, commercially named as CR-39, have been studied. PADC films were exposed to gamma rays at doses ranging from 0.5 to 3 MGy. Gamma exposure induces considerable molecular modifications in PADC films. These modifications were analyzed using Fourier transform infrared (FT-IR) spectroscopy. FT-IR absorption spectra of the gamma irradiated samples show a change in the intensity and the shape of the absorption bands of the chemical groups forming the PADC polymer relative to the pristine one. We have determined G-values for the loss of carbonate ester and ether chemical moieties within PADC. By comparing our G-values with those from other studies, we show that dose rate and dose significantly affect the radiation chemical yields and play an important role of molecular bond kinematics. Highlights: Gamma irradiation has been proposed to study PADC polymer film. Molecular properties of pristine and irradiated PADC detectors were investigated. Radiation chemical yields, G values, for loss of bonds in PADC have been assessed. G values for the loss of carbonate ester and ether bonds are 5.5 and 6.9, respect. Radiation chemical yields are influenced by dose and dose rate of gamma rays.